Self-regulated learning (SRL) dengan prokrastnasi akademik pada siswa akselerasi - Fitria Savira; Yudi Suharsono (Jurnal Ilmiah Psikologi Terapan, 2013)
Procrastination could decrease student's academic achievement. Therefore student should have a good self-control in education by managing time & learning system control that also known in psychologically term as the Self Regulated Learning. The aim of this research is to know the correlation between SRL and academic procrastination of accelerated students. Subjects of the research were student who follow accelerating program in Senior High School at XI grade.The data collected with two scales, SRL scale and academic procrastination scale. The data analyze used product moment correlation. The result showed there was negative and very significant correlation between SRL and academic procrastination with correlation coefficient value is (r)=-0,73 and (P)=0,000.